Myocardial contrast echocardiography in the diagnosis of postoperative takotsubo myocardiopathy: case report and literature review - Jia-Hui Zeng; Wei Li; Feng-Juan Yao; Dong-Hong Liu; Cui-Ling Li; Yan-Qiu Liu; Rui Fan; Min Ye; Hong Lin (BMC Cardiovascular Disorders, 2019)
Abstract Background Takotsubo cardiomyopathy (TCM) is a brief ventricular dysfunction that usually occurs after emotional or physical stress. Here, we report a patient who underwent cardiac surgery and then developed TCM during the postoperative period. Case presentation A 51-year-old woman was admitted to our hospital complaining of chest tightness, palpitations and dyspnoea after activity. An echocardiogram performed by our hospital showed rheumatic heart disease (severe mitral stenosis and regurgitation) with normal cardiac function and wall motion. After mitral valve replacement, this patient developed heart failure with low blood pressure and tachycardia. Urgent bedside echocardiography demonstrated akinesis in the middle and apical segments of the left ventricle and a depressed ejection fraction (EF) of 36%. Myocardial contrast echocardiography (MCE) showed similar enhancement intensity in the basal, middle and apical segments. Quantitative analysis showed approximately equivalent maximum intensity in these regions. The diagnosis was considered TCM instead of myocardial infarction. Then, an intra-aortic balloon pump was inserted to maintain effective circulation and reduce the postcardiac load. Given ventilation therapy, postoperative anticoagulation therapy and anti-infection treatment, the patient recovered quickly. In the follow-up examination, the patient remained asymptomatic and showed normalization of ventricular wall motion in the apical segment. Conclusion This report presents a case of TCM in which MCE was used to demonstrate intact microvascular perfusion despite apical akinesis. This report might support the use of MCE as a substitute for invasive coronary angiography.